Patients who will have an angiography or cateterization procedure: Anxiety factors - Dior Manta Tambunan; Nurhayati Marbun (Science Midwifery, 2023)
Cardiac catheterization is an invasive diagnostic procedure. Cardiac catheterization is an action that can cause anxiety, including worrying about pain related to the procedure, being separated from family and friends and worrying about the results of the catheterization procedure which might be bad. The unclear feeling of Anxiety is fear accompanied by a feeling of uncertainty. The purpose of this study was to determine the factors associated with anxiety in patients undergoing cardiac catheterization. This type of research is descriptive analytic, with total sampling technique and the number of respondents is 40 people. Data analysis used the chi-square test and the Manova test. The results of the study used chi-square found that there was a relationship between anxiety and past experience, education, knowledge, age, and gender, with a p-value <0.005. The Manova test explains that there is a relationship between anxiety and past experience, age and gender with a p-value <0.005. Conversely, there is no relationship between anxiety and education and knowledge with a p-value > 0.005. It is recommended for future researchers to include more samples and add the independent variable family support, because this also affects patient anxiety in undergoing cardiac catheterization.